Implementation of Differentiated Learning Through Cognitive Diagnostic Assessment in Grade IV of SDN 1 Kelayu Jorong - Ramdan, Ahmad Yasar; Muhammad Husni; Hasbialloh (Sumber Belajar Sejahtera, 2024)
This study aims to describe the process of implementing differentiated learning through cognitive diagnostic assessment and factors that can support and hinder teachers. This study used a qualitative research approach with a descriptive research method. The source of this study was fourth grade teacher at SD Negeri 1 Kelayu Jorong. Data collection techniques used interviews, observation, and documentation. Data analysis techniques used data reduction, data presentation, drawing conclusions, and verification. The results of the study showed that the implementation of differentiated learning consists of: 1) Planning stage, mapping students' abilities through cognitive diagnostic assessment results into three learning groups such as: advanced, moderate, and developing groups, and teachers choose and compile teaching materials, methods, and strategies that were in accordance with students' abilities, 2) Implementation stage, used process differentiation, content differentiation, and product differentiation, 3) Evaluation stage, teachers applyed two types of evaluation, namely formative evaluation, and summative evaluation. Supporting factors for the implementation of differentiated learning with teacher collaboration, and the ease of finding sources through PMM. Meanwhile, the inhibiting factors for teachers in implementing differentiated learning were time and lack of encouragement to participate in improving teacher competency through various workshops and seminars.